Stabilization mechanism of white kidney bean based milk through novel perspectives of endogenous starch - Chunli Kong; Yixuan Zhang; Yimei Hu; Caiping Duan; Zheng Yan; Sumei Zhou (Food Chemistry: X)
Plant-based milk (PBM) substitutes have attracted worldwide attention, but the development is restricted by poor stability and limited categories. White kidney bean (WKB) is one potential healthy material for PBM production. Here, we aimed to obtain optimal WKB cultivars first, and further investigated stabilization mechanism in aspect of its endogenous starch. Among the investigated cultivars, three cultivars were selected as the most suitable for producing WKB emulsions. Native starch of the stable cultivars exhibited higher pasting temperature, less peak, trough, and final viscosity. With enzymatic hydrolysis, starch of stable cultivars showed higher solubility index while less swelling power, and less short range order. The observations were further proved through microscopy observation and correlation analysis between starch properties and WKB milk stability attributes. These results contribute to understand molecular mechanism for improving WKB milk stability from perspective of endogenous starch, and provide valuable information for raw materials selection with typical starch characteristics.